An insight into postharvest pericarp browning in litchi (Litchi chinensis Sonn.) - Mir, Hidayatullah; Homa, Fozia; Perveen, Nusrat (Journal of Postharvest Technology, 2015)
Litchi (Litchi chinensis Sonn.), one of the most important  fruits of tropical and subtropical world is highly prized for its  perfectly blended sweet-acidic juicy pulp. The attractive bright  red or pink colour of litchi pericarp which determines the  consumer acceptance is attributed to the presence of a class of  flavonoids, anthocyanin which is lost and turns brown within 2- 3 days of harvesting if stored under ambient conditions.  Post-harvest browning is an important factor limiting the quality  and storage life of litchi fruits and has been attributed mainly to  degradation of anthocyanins, along with the oxidation of phenolic  compounds present in the pericarp by enzymes like polyphenol  oxidase (PPO) and/or peroxidase (POD). Since, PPO, which is  the main enzyme involved in browning has a low affinity to  litchi pericarp anthocyanin, it is supposed that the anthocyanins  are first hydrolysed by anthocyanase, resulting in formation of  anthocyanidin which in turn is oxidized by PPO and/or POD  resulting in oxidative browning. The current research endeavors  focuses on prolonging the shelf life of litchi fruits using  different post-harvest treatments which can maintain the  pericarp membrane integrity thus, avoiding loss of  compartmentalization between litchi pericarp oxidase enzymes  and their substrates and in turn preventing browning.
Keywords: Litchi; Pericarp browning Anthocyanin; Postharvest